Legal aspects of development of formation of Directory of UNR - Грабовська, Ганна Миронівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The creation and development of national education system in period of Dyrektoriya UNR has been examined. The author has been paid attention to democratic basis national education system’s formation.